The Improving Of Students English Pronunciation Skill By Using English Pronunciation Digital At Man Labuhanbatu, SUMUT - Rizki Lestari; Anna Leli Harahap; Diana Munthe; Muhammad Rusli; Shopiah Anggraini Rambe; Nurhanna Harahap (Departement of Mathematics Education, 2024)
The objective of the study is to improve pronunciation skill by using English Pronunciation Digital at MAN Labuhanbatu especially eleventh grade. The population of this study is all eleventh grade with total of 129. In this study, researchers used two classes. They are control class and experimental class and as the sample is XI MIPA 3 as control class with 30 students. The research result showed that using English Pronunciation Digital can improve pronunciation skill. Since the result is proved by t-test is lower than pre-test and post-test that the value of sig 0,000 < at level 0,05. The resulting value t of in the experimental is df29 is 1,699 the resulting t value experimental class is 19,994 then tcount > ttable (19,994> 1,699). While the value of in the control class is 13,750 then tcount> ttable (13,750 > 1,699). From this, it can be concluded that Ha is accepted and Ho is rejected, so that there are any improving the students’ Pronunciation from English Pronunciation Digital on the students’ skill in the class XI MIPA 4.